As uniões simultâneas à luz do direito brasileiro: uma análise doutrinária do princípio da monogamia - Duarte, Jares dos Santos (2023)
The present paper proposes an analysis of monogamy as a principle in the brazilian legal system through doctrinal dialectics, with Tema 529, from the brazilian Federal Supreme Court, as a background, originated from the legal decision which dismissed the Extraordinary Appeal 1.045.273, on the perspective of recognizing the constitution of two or more stable unions as being legally valid family entities. The object has its relevance reflected on the growing interest for the subject by the public opinion, with the ever-growing perception of family arrangements constituted at the form described or variations of it. For the analysis, we used STF’s decision on Tema 529, through the integral text of the Judgment from which it originated, presenting the decisum’s reasoning in opposition to the historical origins, as well as multiple doctrinal understandings on the so-called monogamy principle, outlining the complexity of the many family models possible. The methodology applied on the aforementioned evaluation was the case study, combined with bibliographical analysis.